(untitled) (Revista Brasileira de Contabilidade e Gestão, 2013)
This article presents the project management practice called the Project Office. The main contributions that this practice can offer, the activities developed, and the existing types of Project Offices are addressed. Cases of companies using project office are reported, and the benefits achieved are shown.